Structure–activity relationship study of PROTACs against hematopoietic prostaglandin D2 synthase. Issue 12 (20th October 2022) - Murakami, Yuki; Osawa, Hinata; Kurohara, Takashi; Yanase, Yuta; Ito, Takahito; Yokoo, Hidetomo; Shibata, Norihito; Naito, Mikihiko; Aritake, Kosuke; Demizu, Yosuke
Abstract : SAR studies of PROTACs that target H-PGDS, focusing on the E3 ligase ligand and the H-PGDS ligand, are described. Abstract : Degradation of hematopoietic prostaglandin D2 synthase (H-PGDS) by proteolysis-targeting chimeras (PROTACs) is expected to be important in the treatment of allergic diseases and Duchenne's muscular dystrophy. We recently reported that PROTAC(H-PGDS)- 7 (PROTAC 1 ), which is composed of H-PGDS inhibitor (TFC-007) and cereblon (CRBN) E3 ligase ligand (pomalidomide), showed potent H-PGDS degradation activity. Here, we investigated the structure–activity relationships of PROTAC 1, focusing on the C4- or C5-conjugation of pomalidomide, in addition, the H-PGDS ligand exchanging from TFC-007 with the biaryl ether to TAS-205 with the pyrrole. Three new PROTACs were evaluated for H-PGDS affinity, H-PGDS degrading activity, and inhibition of prostaglandin D2 production. All compounds showed high H-PGDS degrading activities, but PROTAC(H-PGDS)- 4 -TAS-205 (PROTAC 3 ) was slightly less active than the other compounds. Molecular dynamics simulations suggested that the decrease in activity of PROTAC 3 may be due to the lower stability of the CRBN-PROTAC-H-PGDS ternary complex.